Combined Norepinephrine/Serotonergic Reuptake Inhibition: Effects on Maternal Behavior, Aggression, and Oxytocin in the Rat - Cox, Elizabeth T.; Jarrett, Thomas M.; McMurray, Matthew S.; Greenhill, Kevin; Hofler, Vivian E.; Williams, Sarah K.; Joyner, Paul W.; Middleton, Christopher L.; Walker, Cheryl H.; Johns, Josephine M. (Frontiers in Psychiatry, 2011)
Background: Few systematic studies exist on the effects of chronic reuptake of monoamine neurotransmitter systems during pregnancy on the regulation of maternal behavior (MB), although many drugs act primarily through one or more of these systems. Previous studies examining fluoxetine and amfonelic acid treatment during gestation on subsequent MB in rodents indicated significant alterations in postpartum maternal care, aggression, and oxytocin levels. In this study, we extended our studies to include chronic gestational treatment with desipramine or amitriptyline to examine differential effects of reuptake inhibition of norepinephrine and combined noradrenergic and serotonergic systems on MB, aggression, and oxytocin system changes. Methods: Pregnant Sprague-Dawley rats were treated throughout gestation with saline or one of three doses of either desipramine, which has a high affinity for the norepinephrine monoamine transporter, or amitriptyline, an agent with high affinity for both the norepinephrine and serotonin monoamine transporters. MB and postpartum aggression were assessed on postpartum days 1 and 6 respectively. Oxytocin levels were measured in relevant brain regions on postpartum day 7. Predictions were that amitriptyline would decrease MB and increase aggression relative to desipramine, particularly at higher doses. Amygdaloidal oxytocin was expected to decrease with increased aggression. Results: Amitriptyline and desipramine differentially reduced MB, and at higher doses reduced aggressive behavior. Hippocampal oxytocin levels were lower after treatment with either drug but were not correlated with specific behavioral effects. These results, in combination with previous findings following gestational treatment with other selective neurotransmitter reuptake inhibitors, highlight the diverse effects of multiple monoamine systems thought to be involved in maternal care.